2021
DOI: 10.1017/s026357472100148x
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear optimal control approach for underactuated power-line inspection robots

Abstract: The article proposes a nonlinear optimal (H-infinity) control approach for a type of underactuated power-line inspection robots. To implement this control scheme, the state-space model of the power-line inspection robots undergoes first approximate linearization around a temporary operating point, through first-order Taylor series expansion and through the computation of the associated Jacobian matrices. To select the feedback gains of the controller an algebraic Riccati equation is solved at each time step of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…(2) Spatial Feature Tubing. With the rapid development of science and technology, the generation, fabrication, and development of nanomaterials in the UAV robotic power inspection technology gradually formed a good possibility; however, robotic power inspection technology faces with the problem of unclear images of the inspection system, and pixel-level deviation ensures the similarity of the content of two images clarity but ignores the cognitive diferences between the images [12]. Terefore, by acquiring the feature maps of each convolutional layer keyed to the image in the special network model, the L2 spacing between the feature maps of the formed image and the real image is improved according to limiting the high-frequency information content of the formed image and leaving more image key points.…”
Section: Content Loss Functionmentioning
confidence: 99%
“…(2) Spatial Feature Tubing. With the rapid development of science and technology, the generation, fabrication, and development of nanomaterials in the UAV robotic power inspection technology gradually formed a good possibility; however, robotic power inspection technology faces with the problem of unclear images of the inspection system, and pixel-level deviation ensures the similarity of the content of two images clarity but ignores the cognitive diferences between the images [12]. Terefore, by acquiring the feature maps of each convolutional layer keyed to the image in the special network model, the L2 spacing between the feature maps of the formed image and the real image is improved according to limiting the high-frequency information content of the formed image and leaving more image key points.…”
Section: Content Loss Functionmentioning
confidence: 99%
“…By using kinematics modeling and analysis of the working area based on the Monte Carlo approach, the mechanical structure of the robot was optimized. For a particular class of under-actuated power-line inspection robots, Gerasimos Rigatos et al suggested a nonlinear optimum control approach [24].…”
Section: Introductionmentioning
confidence: 99%
“…Power transmission lines inspection is to master the operation status of the line, find out the defects of power facilities and channels along the line in time, and provide data for transmission line maintenance. Compared with traditional manual inspection, transmission line inspection robots have the advantages of low inspection cost, high safety, high reliability, satisfactory inspection in close range, and easy operation [1][2][3][4]. Power line robotics is now considered part of the solution in the evolution of maintenance practices [5,6].…”
Section: Introductionmentioning
confidence: 99%